2023
DOI: 10.1111/mam.12319
|View full text |Cite
|
Sign up to set email alerts
|

Mountain ungulate mating systems: patterns and processes

Abstract: 1. Mountain ungulates of the subfamily Caprinae, including wild sheep, goats and goat-antelopes, show remarkable interspecific diversity in habitat preferences, social organisation and morphological features. We review how this diversity relates to their mating behaviour. 2. After introducing the ecology of mating systems and the evolution of the Caprinae, we investigate the pairwise, sequential relationships between habitat preferences, social behaviour, level of polygyny, and morphological features, and disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 116 publications
1
0
0
Order By: Relevance
“…S8, Supplementary Material online). These values suggest smaller male N e , consistent with the polygynous mating structure in sheep ( Corlatti and Lovari 2023 ). However, the lineages also varied among themselves: we found that the autosomal/chrX diversity ratios were closest to 1 in the N. American/Siberian group, followed by the EUM and ARG.…”
Section: Resultssupporting
confidence: 73%
“…S8, Supplementary Material online). These values suggest smaller male N e , consistent with the polygynous mating structure in sheep ( Corlatti and Lovari 2023 ). However, the lineages also varied among themselves: we found that the autosomal/chrX diversity ratios were closest to 1 in the N. American/Siberian group, followed by the EUM and ARG.…”
Section: Resultssupporting
confidence: 73%